ڈیجیٹل اثاثوں کی میراث: Inheritance of Digital Assets - Muhammad, Ameer; Haque, Dr. M. Ammad ul (Journal of Quranic and Social Studies, 2024)
This research pertains to a legal advancement in the field of inheritance, as the increasing use of the internet and technology has made various services such as email, social media, various websites, digital currencies, and various applications easily accessible to people, bringing convenience and ease to all aspects of life, including education, business, media, marketing, and more. Due to this tremendous progress, we can confidently say that we are living in a digital era. While this revolution has provided humanity with many conveniences, it has also given rise to various legal issues that require attention and solutions, which align with the conditions set by Allah for a Muslim. The challenges arising from these technological revolutions are numerous, but this article will focus on highlighting the legal aspects of digital heritage or "Taraka." In this research, we will delve into the details of this issue, defining digital heritage and discussing its importance for users and their heirs. Additionally, we will clarify user rights concerning digital applications and shed light on the nature of contracts between service providers. We aim to explore the legal consensus on digital heritage through the perspectives and deductions of esteemed jurists.